Investigation of electromagnetic shielding effectiveness of needle punched nonwoven fabrics with staple polypropylene and carbon fibres - SANCAK, ERHAN; ÖZEN, MUSTAFA SABRİ (TAYLOR & FRANCIS LTD, 2016)
Conductive needle punched nonwoven fabrics are developed from staple polypropylene (PP) and varying weight fractions (10, 20 and 30 wt.%) of staple carbon fibres. A fibrous webs of staple PP and carbon fibres were formed at a wool-type carding machine, and these webs subsequently bonded on needle punching machine with 132 punches/cm(2) and 13.5 mm needle penetration depth. The electromagnetic shielding effectiveness (EMSE), absorption and reflection characteristics of as-produced needle punched nonwoven fabrics were determined using a network analyser as specified in ASTM D4935-10 in the frequency range 15-3000 MHz. The surface resistivity measurements were carried out in accordance with ASTM D 257-07 standard. These results indicate that the EMSE values increase incrementally with frequency in the 15-3000 MHz range. The nonwoven sample with 30 wt.% carbon fibre showed the lowest surface resistivity of 3.348 k Omega and corresponding highest EMSE of similar to 42.1 dB in the 3000 MHz frequency range. In comparison, the highest EMSE values from 10 to 20 wt.% staple carbon fibre were found to be 15.6 and 32.2 dB in the 3000 MHz frequency, respectively. It was observed that the absorbance and reflectance curves of each nonwoven fabric move at opposite directions to each other. It was found that as the amount of carbon fibre in the nonwoven fabric increases, absorbance values decrease, but reflectance values increase. The resultant nonwoven fabric samples are expected to be used as garment interlining after thermal bonding and wall interlayer in the future.
Keywords: carbon fibre; polypropylene fibre; electromagnetic shielding; nonwoven; needle punching